Answer:
3√29
Step-by-step explanation:
Use the distance formula to determine the distance between the two points.
Distance
Answer:
2x-12+5=3x-3
1. subtract 3x-2x
-12+5=x-3
2.-12 add to 5
-7=x-3
3. add three to seven
-4=x
Step-by-step explanation:
Answer:
f(1/2) = -2
General Formulas and Concepts:
<u>Pre-Algebra</u>
Order of Operations: BPEMDAS
- Brackets
- Parenthesis
- Exponents
- Multiplication
- Division
- Addition
- Subtraction
<u>Algebra I</u>
Step-by-step explanation:
<u>Step 1: Define</u>
f(x) = 8x - 6
f(1/2) is x = 1/2
<u>Step 2: Evaluate</u>
- Substitute in <em>x</em>: f(1/2) = 8(1/2) - 6
- Multiply: f(1/2) = 4 - 6
- Subtract: f(1/2) = -2
Answer:
x = 15
Step-by-step explanation:
Since the triangles are similar then the ratios of corresponding sides are equal, that is
BC/DC = EC/AC , substitute values
3x×5/32 - 5x-5/56 ( cross- multiply )
56(3x - 5) = 32(5x - 5) ← distribute and simplify both sides
168x - 280 = 160x - 160 ( subtract 160x from both sides )
8x - 280 = - 160 ( add 280 to both sides )
8x = 120 ( divide both sides by 8 )
x = 15
Answer:
x = -7/4
General Formulas and Concepts:
<u>Pre-Algebra</u>
Order of Operations: BPEMDAS
- Brackets
- Parenthesis
- Exponents
- Multiplication
- Division
- Addition
- Subtraction
Equality Properties
- Multiplication Property of Equality
- Division Property of Equality
- Addition Property of Equality
- Subtract Property of Equality
<u>Algebra I</u>
Step-by-step explanation:
<u>Step 1: Define</u>
5x + 3 - 2x = 12 + 7x - 2
<u>Step 2: Solve for </u><em><u>x</u></em>
- Combine like terms: 3x + 3 = 7x + 10
- [SPE] Subtract 3x on both sides: 3 = 4x + 10
- [SPE] Subtract 10 on both sides: -7 = 4x
- [DPE] Divide 4 on both sides: -7/4 = x
- Rewrite: x = -7/4
<u>Step 3: Check</u>
<em>Plug in x into the original equation to verify it's a solution.</em>
- Substitute in <em>x</em>: 5(-7/4) + 3 - 2(-7/4) = 12 + 7(-7/4) - 2
- Multiply: -35/4 + 3 + 7/2 = 12 - 49/4 - 2
- Add: -23/4 + 7/2 = 12 - 49/4 - 2
- Add: -9/4 = 12 - 49/4 - 2
- Subtract: -9/4 = -1/4 - 2
- Subtract: -9/4 = -9/4
Here we see that -9/4 does indeed equal -9/4.
∴ x = -7/4 is the solution to the equation.